Communicating prognosis and end-of-life care to heart failure patients: A survey of heart failure nurses' perspectives. (April 2014) - Hjelmfors, Lisa; Strömberg, Anna; Friedrichsen, Maria; Mårtensson, Jan; Jaarsma, Tiny
Background: Many heart failure (HF) patients have palliative care needs, but communication about prognosis and end-of-life care is lacking. HF nurses can play an important role in such communication, but their views on this have rarely been sought. Aims: This study aims to describe HF nurses' perspectives on, and daily practice regarding, discussing prognosis and end-of-life care with HF patients in outpatient care. It further aims to explore barriers, facilitators and related factors for discussing these issues. Methods: A national survey including nurses from outpatient clinics and primary health care centres was performed. Data was collected using a questionnaire on communication with HF patients about prognosis and end-of-life care. Results: In total, 111 (82%) of the HF nurses completed the questionnaire. Most of them reported that physicians should have the main responsibility for discussing prognosis (69%) and end-of-life care (67%). Most nurses felt knowledgeable to have these discussions, but 91% reported a need for further training in at least one of the areas. Barriers for communication about prognosis and end-of-life care included the unpredictable trajectory of HF, patients' comorbidities and the opinion that patients in NYHA class II-III are not in the end-of-life. Conclusion: Although HF nurses feel competent discussing prognosis and end-of-life care with the HF patient, they are hesitant to have these conversations. This might be partly explained by the fact that they consider the physician to be responsible for such conversations, and by perceived barriers to communication. This implies a need for clinical policy and education for HF nurses to expand their knowledge and awareness of the patients' possible needs for palliative care.